MONITORING KEBIJAKAN PELAYANAN PARKIR DI TEPI JALAN UMUM DAERAH KOTA BENGKULU - Rekho Adriadi; Faizal Anwar; Yogi Alfiansyah (Jurnal Caraka Prabu, 2019)
This paper examines the Policy for Parking Services Policies on the Side of Public Roads in Bengkulu City as a result of the monitoring results from the analysis of the implementation of Parking Service Policies on Public Roadside of Bengkulu City In the implementation of the parking service retribution policy in Bengkulu city, the standards and procedures are clear, but in the field implementation, especially the Panorama area is still there. The targets in this policy are in accordance with Perda no. 07 of 2011. Implementation of parking policies that affect the social conditions of the people in the city of Bengkulu with the number of parking spots is the stage of the Bengkulu city community. However, during the crisis there was still a mismatch of income results and targets in this policy due to the low parking potential in the city of Bengkulu. Keywords: Policy, Parking, Retribution